THE ROLE OF CONSUMER LENDING IN THE ACTIVITY OF COMMERCIAL BANKS IN THE REPUBLIC OF UZBEKISTAN. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The article analyzes the importance of consumer lending in the banking sector, the state of development of this type of activity, and at the end of the article the author offers suggestions and recommendations for its further development. Also analyzes the opinions expressed in research conducted on this topic and refers to research conducted by researchers in the field of consumer credit development.